Variação sazonal na composição química da água no leito principal do Rio Amazonas em frente à cidade de Óbidos-PA - MITSUYA, Miyuki (Universidade Federal do Oeste do Pará, 2021)
Rivers are important sources of information about what occurs in the drainage basin. Inland waters are important processors of organic carbon, because they transport, mineralize and bury approximately 2,7 Pg C per year, an amount equivalent to the size of the terrestrial carbon sink for anthropogenic emissions. Despite the emerging recovery, there are few data on the connections between the cycle of terrestrial and aquatic carbon currently to the Amazon River. In this context, the aim of this study was to quantify land-ocean carbon flux of the Amazon River transiting at the narrowest point of its mainstem. In the perspective of estimating also the loads of Nitrogen and Total Dissolved nutrients, observing their variations in two years of hydrological cycle. Monthly samples of surface water from the Amazon River were held in front of the city of Óbidos-PA during the period 2012-2013. Samples were filtered (filter <0,45 μm) and frozen until the shipment to analysis in the Woods Hole Research Center (Falmouth, MA, USA). To quantify the concentrations of the studied variables, Shimadzu TOC-V was used in combination with a TNM-1 for total organic carbon and nitrogen dissolved total. Nutrient analysis was performed by colorimetric detection in an Astoria®Analyzer. And to estimate loads, the program LOADEST (LOAD ESTimator) was used. The average total charge over of dissolved organic carbon was 29,85 TgC ano-1, Total Dissolved Nitrogen with 2,355 TgN ano-1. The Phosphate (PO4) was quantified with 0,08 TgP in both years. And Silicate (SiO2) showed total average amount of 59,75 Tg ano-1 for the biennium 2012-2013. Significant differences (p<0,05) were found between the stations of hydrograph from the point of view of intra and inter annual for some of the variables . Although the increase of freight transportation as the COD and SiO2 has been observed, compared with values recorded, it emphasizes the importance of continuing the monthly measurements for the formation of a consistent baseline and current loads carried over from the Amazon River to its mouth, as there are indications that the contribution of the Amazon region has been underestimated in the overall balance.